The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12864-022-08767-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and identification of the PEBP genes of Brassica juncea var. Tumida

Abstract: Background Phosphatidylethanolamine-binding protein (PEBP) is widely present in animals, plants, and microorganisms. Plant PEBP genes are mainly involved in flowering transition and nutritional growth. These genes have been studied in several plants; however, to the best of our knowledge, no studies have explored them in Brassica juncea var. tumida. This study identified and characterized the entire PEBP gene family of Brassica juncea var. tumida. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
2
1
0
Order By: Relevance
“…Regarding amphidiploids, the presence of twelve genes suggests these species inherited six genes from each of their parental species, corresponding to the GTR genes found in Arabidopsis [42]. This is in line with the previous research conducted on other gene families of B. juncea which showed that the allotetraploid Brassicas attained genes approximately three times more than Arabidopsis [72]. Similar observations of gene duplications have been reported in other polyploid crops, such as cotton and wheat [74,75].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding amphidiploids, the presence of twelve genes suggests these species inherited six genes from each of their parental species, corresponding to the GTR genes found in Arabidopsis [42]. This is in line with the previous research conducted on other gene families of B. juncea which showed that the allotetraploid Brassicas attained genes approximately three times more than Arabidopsis [72]. Similar observations of gene duplications have been reported in other polyploid crops, such as cotton and wheat [74,75].…”
Section: Discussionsupporting
confidence: 88%
“…The presence of cis-regulatory elements associated with signalling molecules like JA, SA, and related elements suggests a role for GTR genes in stress conditions, highlighting a degree of specificity. This observation reinforces the concept of neofunctionalization occurring after genome duplication and triplication during speciation and evolution [72].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation